OPTIMIZATION OF RENEWABLE ENERGY BASED SMART MICROGRID SYSTEM FOR ICE BLOCK MACHINE POWER SUPPLY - Musfirin
This research was conducted with the purpose of optimizing the smart microgrid system based on renewable energy in the Kemujan Village, Karimunjawa District. From this optimization the system become more reliable and efficient to supply the electrical energy consumption for the ice block making machine. The results of the optimization of smart microgrid system will be analyzed to determine the performance, power distribution and production cost of making ice block and also analyzing performance rasio of photovoltaic. This smart microgrid is designed by utilizing components that have been installed on site, such as 5 kWp Photovoltaic, 4 kW generator and 12 V batteries, 80 Ah, 20 pieces.